Answer:
a₄ = 12
Step-by-step explanation:
To obtain the terms in the sequence add 2 to the previous term, that is
a₂ = a₁ + 2 = 6 + 2 = 8
a₃ = a₂ + 2 = 8 + 2 = 10
a₄ = a₃ + 2 = 10 + 2 = 12
Answer:
X1= -1, X2= 2
Step-by-step explanation:
find the x-intercept/zero
hope this helps:)))
Answer:
wag kana mag aral lol
Step-by-step explanation:
sungin mo module mo
<u>Answer</u>:
Jared is right.
<u>Explanation</u>:
proof 1:
10 - 4 = 6
6 = 6
second proof:
10-3 - 4 = 6 - 3
10 - 7 = 3
3 = 3
third proof:
10 - 4 - 3 = 6 - 3
10 - 7 = 3
3 = 3
Hence for all LHS = RHS proved and Jared is correct.